2019
DOI: 10.3389/fimmu.2019.02521
|View full text |Cite
|
Sign up to set email alerts
|

Functions of the WNT Signaling Network in Shaping Host Responses to Infection

Abstract: It is well-established that aberrant WNT expression and signaling is associated with developmental defects, malignant transformation and carcinogenesis. More recently, WNT ligands have emerged as integral components of host responses to infection but their functions in the context of immune responses are incompletely understood. Roles in the modulation of inflammatory cytokine production, host cell intrinsic innate defense mechanisms, as well as the bridging of innate and adaptive immunity have been described.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 210 publications
2
57
0
Order By: Relevance
“…To identify which pathways are associated with SARS-CoV and SARS-CoV infection, we have performed the gene ontology (GO) and pathway functional enrichment of the targeted genes using different tools. This revealed a myriad of significant functions and pathways involved in host immune responses, such as Wnt signaling (Ljungberg et al, 2019 ), MAPK signaling (Kimura et al, 2013 ), T-cell-mediated immunity (Channappanavar et al, 2014 ), autophagy (Yordy and Iwasaki, 2011 ), FGF receptor binding (van Asten et al, 2018 ), TGF-beta signaling (Denney et al, 2018 ), VEGF signaling (Alkharsah, 2018 ), ErbB signaling (Zheng et al, 2014 ), mTOR signaling (Le Sage et al, 2016 ), and TNF-alpha signaling (Kimura et al, 2013 ) are particularly targeted by SARS-CoV-2 ( Figures 7A–E ).…”
Section: Resultsmentioning
confidence: 99%
“…To identify which pathways are associated with SARS-CoV and SARS-CoV infection, we have performed the gene ontology (GO) and pathway functional enrichment of the targeted genes using different tools. This revealed a myriad of significant functions and pathways involved in host immune responses, such as Wnt signaling (Ljungberg et al, 2019 ), MAPK signaling (Kimura et al, 2013 ), T-cell-mediated immunity (Channappanavar et al, 2014 ), autophagy (Yordy and Iwasaki, 2011 ), FGF receptor binding (van Asten et al, 2018 ), TGF-beta signaling (Denney et al, 2018 ), VEGF signaling (Alkharsah, 2018 ), ErbB signaling (Zheng et al, 2014 ), mTOR signaling (Le Sage et al, 2016 ), and TNF-alpha signaling (Kimura et al, 2013 ) are particularly targeted by SARS-CoV-2 ( Figures 7A–E ).…”
Section: Resultsmentioning
confidence: 99%
“…We found that CD73+ CD4+ and CD8+ T cells include effector cells with high expression of TCF-1, which has also been demonstrated in murine quiescent memory T cells that are capable of proliferative responses in response to recall antigens [ 30 ]. TCF-1 is integral to Wnt/β-catenin signaling, but whether this signaling pathway is involved in memory T cell differentiation is still unclear [ 29 , 55 , 56 ]. High TCF-1 expression is also maintained during homeostatic proliferation [ 29 ], as we similarly found with maintenance of CD73 expression during IL-7 driven proliferation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…To identify which pathways are associated with SARS-CoV and SARS-CoV infection, we have performed the gene ontology (GO) and pathway functional enrichment of the targeted genes using different tools. This reveals a myriad of significant functions and pathways involved in host immune responses, like-Wnt signaling (Ljungberg et al, 2019), MAPK signaling (Kimura et al, 2013), T cell-mediated immunity (Channappanavar et al, 2014), autophagy (Yordy and Iwasaki, 2011), FGF receptor binding (van Asten et al, 2018), TGF-beta signaling (Denney et al, 2018), VEGF signaling (Alkharsah, 2018), ErbB signaling (Zheng et al, 2014), mTOR signaling (Le Sage et al, 2016), TNF-alpha signaling (Kimura et al, 2013), etc are particularly targeted by SARS-CoV-2 (Figure 7A-7E).…”
Section: Resultsmentioning
confidence: 99%